Effect of five year storage on total phenolic content and antioxidant capacity of almond (Amygdalus communisL.) hull and shell from different genotypes - Khadijeh Sadat Moosavi Dolatabadi; Gholamreza Dehghan; Siavash Hosseini; Ali Jahanban Esfahlan (Mashhad University of Medical Sciences, 2014)
Objectives: Almond (Prunus amygdalus) hull and shell are agricultural by-products that are a source of phenolic compounds.The processing of almond produce shell and hull, accounts for more than 50% by dry weight of the almond fruits. Recently, more studies have focused on the influence of storage conditions and postharvest handling on the nutritional quality of fruits, especially the antioxidant phenolics. In this study, influence of long-term storage (five years) on the total phenolic and antioxidant capacity of almond hull and shell from different genotypes was evaluated. Materials and Methods: The fruits of subjected genotypes were collected and their hull and shell were separated. They were dried and reduced to fine powder. This powder stored at room temperature for five years. The total phenolic content (TPC) and bioactivities (antioxidant potential: DPPH and ABTS radical scavenging and reducing power) of extracts were evaluated using spectrophotometric methods. Results: It was found that TPC content and bioactivity levels in the stored almond hull and shell were different, compared to the hulls and shells which were evaluated in 2007. S1-4 genotype had the highest TPC and reducing power in its hull and shell.Low correlation coefficient was observed between phenolic content and the DPPH radical scavenging percentage in hull and shell extract. Conclusions: For the first time, results of this investigation showed that storage can influence the antioxidant and antiradical potential of almond hull and shell.